Factors associated with temporomandibular disorders pain in adolescents - Fernandes, Giovana [UNESP]; van Selms, Maurits K. A.; Gonçalves, Daniela Aparecida de Godoi [UNESP]; Lobbezoo, Frank; Camparis, Cinara Maria [UNESP] (Wiley, 2015)
To gain a better understanding of temporomandibular disorders (TMD) pain in adolescents, it is important to study the factors associated with its presence. Therefore, the aim of this study was to investigate potential predictors for TMD pain in adolescents, thereby including a diversity of factors from the biopsychosocial model to determine the strongest predictors. The sample of this cross-sectional study consisted of 1094 adolescents. The presence of TMD pain was assessed using the RDC/TMD, Axis I. Apart from demographical characteristics, the roles of parafunctional habits, psychosocial aspects, menarche and other bodily pain complaints were evaluated. Single and multiple logistic regression models were used to identify associations between the predictor variables and TMD pain. Painful TMD had a prevalence of 25·5%. Logistic regression analyses showed that TMD pain was associated with sleep bruxism (OR = 1·8 95% CI = 1·34–2·34), awake bruxism (OR = 2·1 95% CI = 1·56–2·83), other parafunctional habits (OR = 2·2 95% CI = 1·17–4·08) and bodily pain complaints (OR = 5·0 95% CI = 3·48–7·28). Parafunctional habits and other bodily pain complaints may play an important role in the presence of TMD pain in adolescents. Of course, it remains unclear whether the observed associations between the investigated factors and the adolescent's TMD pain have a true causal linkage.
Keywords: TMD pain; Adolescents; Bruxism; Psychosocial factors; Bodily pain